Protection by serum antibodies in experimental nontypable Haemophilus influenzae otitis media. - Barenkamp, S J (1986)
The chinchilla experimental model of otitis media was used to examine the importance of serum antibodies in protection against disease caused by nontypable Haemophilus influenzae. An immune serum pool was prepared by immunizing chinchillas with killed bacterial cells of nontypable H. influenzae 3245. Pooled preimmune or immune serum from these immunized animals was administered intravenously to a group of nonimmune chinchillas 1 day before intrabullar challenge with strain 3245. Of 5 animals receiving preimmune serum, 5 developed otitis media compared with 0 of 10 animals receiving immune serum (P = 0.008). The immune serum pool contained antibodies directed against both surface-exposed outer membrane proteins and lipopolysaccharide (LPS). The 39-kilodalton major outer membrane protein was the immunodominant surface protein. Anti-LPS antibodies were removed from the immune serum pool by affinity chromatography, and affinity-purified anti-LPS antibodies were recovered. Immune serum, immune serum absorbed of LPS antibodies, or affinity-purified LPS antibodies were then administered to another group of experimental animals 1 day before bacterial challenge. Of four animals that received the affinity-purified LPS antibodies, four developed otitis compared with zero of four animals that received the immune serum or zero of four animals that received the LPS-absorbed immune serum (P = 0.028). These studies indicate that passive immunization with immune serum is protective in experimental nontypable H. influenzae otitis media and that bacterial outer membrane proteins may be the principal targets of protective antibody.